2009
DOI: 10.1158/0008-5472.can-08-3901
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PDE4D as a Proliferation Promoting Factor in Prostate Cancer Using a Sleeping Beauty Transposon-Based Somatic Mutagenesis Screen

Abstract: Retroviral and transposon-based mutagenesis screens in mice have been useful for identifying candidate cancer genes for some tumor types. However, many of the organs that exhibit the highest cancer rates in humans, including the prostate, have not previously been amenable to these approaches. This study shows for the first time that the Sleeping Beauty transposon system can be used to identify candidate prostate cancer genes in mice. Somatic mobilization of a mutagenic transposon resulted in focal epithelial p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 52 publications
(71 reference statements)
3
67
0
Order By: Relevance
“…Miething et al (2007) further explored RUNX3's cancer function in leukemia when they incorporated a drug used for treatment of Bcr-Abl-expressing leukemia, imatinib, in their retroviral mutagenesis screen-they showed that insertion of a retroviral element in the vicinity of the RUNX3 promoter results in elevated RUNX3, which in turn led to increased resistance to imatinib-induced apoptosis and thus chronic myeloid leukemia (Miething et al, 2007). Runx3 was also identified as a cancerassociated gene by Sleeping Beauty transposable elements-transposon integration at the 5 0 position of the RUNX3 gene was associated with T-cell lymphoma (Dupuy et al, 2005) and prostate cancer (Rahrmann et al, 2009 Altogether, these findings suggest that while RUNX3 inactivation is a major determinant of cancer pathogenesis (see Table 1) and clinical outcome in many cancer types, in certain tumor types, overexpression of RUNX3 is oncogenic. In other words, RUNX3 mediates context-dependent tumor suppression.…”
Section: Insertional Mutagenesis Screen Implicates Runx3 In Tumor Devmentioning
confidence: 99%
“…Miething et al (2007) further explored RUNX3's cancer function in leukemia when they incorporated a drug used for treatment of Bcr-Abl-expressing leukemia, imatinib, in their retroviral mutagenesis screen-they showed that insertion of a retroviral element in the vicinity of the RUNX3 promoter results in elevated RUNX3, which in turn led to increased resistance to imatinib-induced apoptosis and thus chronic myeloid leukemia (Miething et al, 2007). Runx3 was also identified as a cancerassociated gene by Sleeping Beauty transposable elements-transposon integration at the 5 0 position of the RUNX3 gene was associated with T-cell lymphoma (Dupuy et al, 2005) and prostate cancer (Rahrmann et al, 2009 Altogether, these findings suggest that while RUNX3 inactivation is a major determinant of cancer pathogenesis (see Table 1) and clinical outcome in many cancer types, in certain tumor types, overexpression of RUNX3 is oncogenic. In other words, RUNX3 mediates context-dependent tumor suppression.…”
Section: Insertional Mutagenesis Screen Implicates Runx3 In Tumor Devmentioning
confidence: 99%
“…11). Interestingly, a previous study using a sleeping beauty transposon-based screen suggested that PDE4D might function as a proliferation promoting factor in prostate cancers (12). Very recently, Pullamsetti et al found that cross-talk that occurred between PDE4 and hypoxia induciblefactor signaling might promote angiogenesis in lung cancer (13).…”
mentioning
confidence: 99%
“…Although the overexpression of PDE4D was generally associated with STK11 mutation in most cell lines, only lung category was appropriate for the association study with statistical confidence. PDE4D has been implicated in cancer cell proliferation and metastasis (27,28). The inhibition of PDE4 activity suppressed cell growth and induced apoptosis in human leukemia cells (29).…”
Section: Resultsmentioning
confidence: 99%